The traditional and the new social studies in secondary schools of Greater Manila its implications for the secondary schools of Hong Kong - Ng, Louis Kai-Gay 1934- (s.n.], 1971)
This is a descriptive study on how social studies is being taught using the new and the traditional approaches.This study sought to find out how the traditional social studies and the new social studies are being taught in some selected schools in Greater Manila and to draw implications for the schools in Hong Kong.